2019
DOI: 10.1155/2019/5198583
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Strength of Rubberized Concrete by an Evolved Random Forest Model

Abstract: Rubberized concrete (RC) has attracted more attention these years as it is an economical and environmental-friendly construction material. Normally, the uniaxial compressive strength (UCS) of RC needs to be evaluated before application. In this study, an evolutionary random forest model (BRF) combining random forest (RF) and beetle antennae search (BAS) algorithms was proposed, which can be used for establishing the relationship between UCS of RC and its key variables. A total number of 138 cases were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 46 publications
(41 reference statements)
0
31
0
1
Order By: Relevance
“…From results, it was found that RF showed reduced performance in comparison to other models. In a study conducted by Sun et al [21], the authors utilized RF combined with an optimization algorithm for predicting the uniaxial compressive strength of rubberized concrete. e output of the study reported good accuracy of the model with a high correlation.…”
Section: Introductionmentioning
confidence: 99%
“…From results, it was found that RF showed reduced performance in comparison to other models. In a study conducted by Sun et al [21], the authors utilized RF combined with an optimization algorithm for predicting the uniaxial compressive strength of rubberized concrete. e output of the study reported good accuracy of the model with a high correlation.…”
Section: Introductionmentioning
confidence: 99%
“…e present study aims to propose a robust machine learning technique to be used as a tool to predict the permeability of pervious concrete. An efficient global optimization algorithm (called the beetle antennae search, BAS) proposed by Jiang et al was adopted in this study to obtain the optimized parameters of RF [37]. In this way, the random forest (RF) and beetle antennae search (BAS) algorithms were combined to build a robust machine learning technique, named as BRF method.…”
Section: Research Objective and Overviewmentioning
confidence: 99%
“…However, no corresponding studies were reported to use RF to predict the permeability of pervious concrete so far. Besides, as far as the RF model employed in the previous studies, the hyperparameters were still required to be optimized to arrive at their optimized predictive ability [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning methods have been widely used for predicting the mechanical properties of construction materials [12,[17][18][19][20][21][22][23]. e assessment of the strength of CPB by artificial intelligence methods has also been presented.…”
Section: Introductionmentioning
confidence: 99%